Kamishibai dan Propaganda Jepang di Jawa pada Masa Perang Asia Timur Raya - Budiarto, Gema; Yuliati, Dewi; Puguh, Dhanang Respati (Department of History, Faculty of Humanities, Diponegoro University, 2023)
During the war, the Japanese military occupation government of Java utilized various propaganda media to mobilize the Javanese people to support the war effort. One such medium was kamishibai, or picture story shows, which was introduced to Javanese society by Japan. Throughout the wartime period, the themes of kamishibai stories were controlled and dictated by the Japanese military government. As a form of propaganda media presented through performing arts, kamishibai effectively reached audiences of all ages, from children to adults. This article explores kamishibai as a visual performance art serving as propaganda in Javanese society during the Greater East Asian War. Employing historical research methodology, this study investigates the role of kamishibai in conveying specific messages, particularly those related to supporting the war effort. The findings of this research reveal that kamishibai, originally a Japanese performing art, was utilized by the Japanese military occupation government in Java to disseminate certain messages, particularly those aimed at boosting morale and spirit. The themes depicted in kamishibai stories often focused on efforts to uplift people's morale, glorify the Japanese Empire, foster anti-Western sentiment, and promote labor efforts.